(untitled) (Research, Society and Development, 2022)
This study aimed to analyze trends in Brazilian scientific production on the health of workers who work in the prison system. This is a narrative review, developed with theses and dissertations from the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel and from the Brazilian Digital Library of Theses and Dissertations held in July and August 2021. The result was 177 productions, after applying the inclusion and exclusion criteria, the corpus totaled 19 studies. Most of the works are dissertations (73.7%), with the highest number in 2017, with 52.6% of the works carried out with Penitentiary Security Agents, by the graduate programs of Psychology and Nursing, 31.5% and 15.7%, respectively, with a predominance of qualitative studies (78.9%). Regarding the health of workers in the prison system, the productions identified the following conditions: 42.1% showed that workers felt fear and insecurity and perceived the prison environment as stressful; in 36.8% the environment was perceived as precarious, unhealthy, with inadequate infrastructure and poor working conditions; in 15.8% of them, it was found that the employees had a high demand for work and that they were not adequately trained to work in prisons; 10.5% reported a stigma related to work, that workers had common mental disorders, overcrowded prisons and a violent work environment. A complex, unhealthy work context and the lack of research with proposals for improvements in work processes, strategies for health promotion and disease prevention in this professional category are evident.